Utilization of Chrysanthemum Leaf Extract and Molasses in the Cultivation of Chrysanthemum Cut Flowers - I Gusti Made Arjuna; A.A. Putri Risa Andriani (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
This research aims to determine the effect of extraction of chrysanthemum and molasses leaves and their interactions on growth and yield in the cultivation of chrysanthemum cut flowers. The research method uses a randomized block design of factorial patterns with two factors, namely: extract of chrysanthemum leaves consisting of four levels each: 250 g l-1, 500 g l-1, 750 g l-1 and 1000 g l-1, as well as molasses consists of three levels respectively: 5 ml l-1, 10 ml l-1 and 15 ml l-1. The combination treatment of 12 was repeated 3 replications. The results showed that the interaction between the extraction of chrysanthemum leaves and molasses had not significantly affected on all the observed variables. The extraction treatment of chrysanthemum leaves has a significant effect (P˂0.05) to very significant (P ˂ 0.01) on all observed variables except at maximum plant height and stem diameter. The extraction treatment of chrysanthemum leaves 1000 g l-1 resulted in the average fresh weight of flower stalks and the highest economic fresh weight of 133.67 g and 110.27g respectively. There was an increase in yield by 24.99% and 26.71% when it was compared to the lowest treatment. Molasses treatment exerts a significant effect (P ˂ 0.05) to a very significant (P ˂ 0.01) influence on all observed variables, except on the diameter of the rod. Molasses treatment of 15 ml l-1 resulted in an average fresh weight of flower stalks and the highest economic fresh weight of 120.79 g and 94.51 g compared to the lowest treatment, and there was an increase in yield by 11.86% and 25.51% compared to the lowest treatment